Studies on a higher pure thermo-enrichment converting anaerobically and directly cellulose to ethanol - LÜ Fu-ying; MIN Hang; CHEN Mei-ci; LIU Ying (浙江大学学报. 农业与生命科学版)
A thermo-enrichment which could anaerobically and directly convert cellulose to ethanol was obtained from fresh cow manure by Hungate anaerobic technique. The dominant species in the enrichment is a bacterium in Clostridium, with size of 0.54 μm x 4.86～9.72 μm, G+, round spore with diameter of 0.86～1.19 µm. The optimal temperature was 55℃ to 60℃ and the optimal pH was 7.5 for formation of ethanol. The enrichment could converse directly rice and wheat straw to ethanol with the highest ethanol concentrations of 0.257 g/L and 0.129 g/L, respectively.